Investigating EFL Saudi University Students’ Reading and Online Habits and Interests - khreisat, Mohammad (International Journal of Language and Literary Studies, 2023)
This study examines the English reading habits and online activities of Saudi English language university students, the types of reading they undertake and potential reasons for their lack of reading. A questionnaire was used to collect data for this study as the primary tool for quantitative research. To evaluate the impact of the Saudi College of Arts and Science at Tabarjal, Jouf University on Saudi EFL university students, a self-administered online questionnaire was distributed to an online sample of 158 Saudi EFL university students. In free time, students read textbooks and online articles most often. In addition, students reported spending more than six hours online using social media apps. This study recommends to provide more reading resources at the institution to promote reading among students.